ANALISIS PENGARUH PERUBAHAN KONSENTRASI SURFAKTAN DAN SOAKING TERHADAP FAKTOR PEROLEHAN MINYAK DARI MODEL SATU DIMENSI RESERVOIR SANDSTONE DENGAN METODE CORE FLOODING (STUDI LABORATORIUM) - Kunto Baskoro, Ibrahim
With increasing world oil demand, it is a necessary to improve the production from the brown field by the EOR (Enhanced Oil Recovery) method, and surfactant injection is one of that method. Surfactants are organic compounds that can lower the oil-water interfacial tension and the effect is improving the displacement efficiency and altering rock wettability so the oil trapped in rock pores easier to be pushed out. This laboratory study aimed to see how is the effect of concentration alteration and soaking process of the type of surfactant that has been selected on the oil recovery factor of one-dimensional model of sandstone reservoir by core flooding method that supported by analysis of injection water, viscosity, porosity, and permeability. This laboratory study consisted of two main processes, imbibition test and core flooding. Imbibition test was conducted in order to select the best suitable type of surfactant applied to the sandstone reservoir model. By comparing the performance of water injection and three types of surfactants, namely S13A * (non-ionic), S1 (anionic), and S4 (anionic-cationic blend) at a concentration of 0.5 wt%, this test obtain that S1 has the best performance with RF (Recovery Factor) maximum value of 41.69% and this surfactant will be used for the core flooding. Core flooding with the core along 29 cm and at a temperature of 70 ° C was started with water flooding then surfactant flooding. Surfactant flooding that consist of two-phase injection has four scenarios are applied to four different cores, two increased concentration scenarios (0.5%-2%) and two decreased concentration scenarios (2% -0.5%), by applying the soaking method of surfactant phase I injection in one of two scenarios increased and decreased concentration. The experimental results show that the decreased concentrations scenario with soaking method of 2 % wt surfactant concentrationis the best scenario with RF value of 61.85%.